Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.06.11.146407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doxycycline has Distinct Apicoplast-Specific Mechanisms of Antimalarial Activity

Abstract: Doxycycline (DOX) is a key antimalarial drug that is thought to kill Plasmodium falciparum parasites by blocking protein translation in the essential apicoplast organelle. Although parasite resistance to DOX has not emerged, clinical use is primarily limited to prophylaxis due to delayed second-cycle parasite death at 1-3 μM, the DOX concentration readily achieved in human plasma at current dosing. Slow antiparasitic activity is thought to be a fundamental limitation of DOX and other antibiotics that target ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Parasite growth assays: All parasite studies were performed with P. falciparum Dd2 parasites cultured in RPMI-1640 medium as previously described (58) For bacteria expression studies, BL21/DE3 E. coli were transformed with pET plasmids encoding cloned P. falciparum mACP-HA2 (full-length or the ∆2-50 truncation, WT or F113A mutant), Isd11-His6 (WT, YR/AA, or LYR/AAA mutants), or full-length Nfs1-HA2. Protein expression was induced by 1 mM IPTG, and bacterial pellets were lysed in PBS by sonication and clarified by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasite growth assays: All parasite studies were performed with P. falciparum Dd2 parasites cultured in RPMI-1640 medium as previously described (58) For bacteria expression studies, BL21/DE3 E. coli were transformed with pET plasmids encoding cloned P. falciparum mACP-HA2 (full-length or the ∆2-50 truncation, WT or F113A mutant), Isd11-His6 (WT, YR/AA, or LYR/AAA mutants), or full-length Nfs1-HA2. Protein expression was induced by 1 mM IPTG, and bacterial pellets were lysed in PBS by sonication and clarified by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…All parasite studies were performed with P. falciparum Dd2 parasites cultured in RPMI-1640 medium as previously described (64). CRISPR/Cas9 was used to tag the mACP gene in Dd2 parasites to encode a C-terminal HA-FLAG epitope tag and the aptamer/TetR-DOZI system (30), whose integration was validated by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The apicoplast is involved in the synthesis of isoprenoids ( Tewari et al, 2021 ) from isopentenyl pyrophosphate (IPP) in the blood stage of the parasite ( Miller et al, 2014 ; Rai et al, 2017 ). Inhibitors of prokaryotic DNA replication (ciprofloxacin), prokaryotic translation (chloramphenicol, doxycycline ( Okada et al, 2020 ), tetracycline, clindamycin, azithromycin, erythromycin and clarithromycin), a tRNA synthase (mupirocin), and IPP synthesis pathway (fosmidomycin and FR900098) are regarded as targets of apicoplasts ( Uddin et al, 2018 ). Kumarihamy et al (2020) showed that the in vitro antimalarial activity of Botryosphaeria dothidea was due to the common metabolic pathway shared by the apicoplast in Plasmodium parasites and plastids in plants.…”
Section: Invasion and Egress Of Merozoites And Inhibitionmentioning
confidence: 99%